A MILP based Optimization and FPGA Implementation of Efficient Polyphase Multirate Filters - Gopal S. Gawande, Dhanraj R. Dhotre, Nitin Choubey, Dipali S. Mate (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Effectively implementing digital filters at cheap cost is made possible by the DSP field’s multirate filtering method. By taking advantage of concurrency in multirate digital filters, the processing burden of polyphase decomposition techniques is reduced. Since each positive bit requires an extra adder in circuitry execution and more toggling at the end of CMOS circuits, reducing the number of positive terms in the filter coefficients is a primary focus of filter improvement. In order to lessen the quantity of nonzero factors in the filter coefficients, an innovative method is proposed in this article. Polyphase shapes are used to test the suggested algorithm’s effects on power usage. The constructions are manufactured for Spartan6 xc6slx150T-4fgg676 FPGA panel consuming system generator for obtaining the other performance indices like throughput, speed, logic area and computation rate. In spite of occupying more area, efficient polyphase decimator structure is found to be superior to the polyphase and decimation structures.